How Do Students Perceive Grammar Learning Through Quizizz Insight From Eleventh Graders - Anita Lucy Nurhalyza; Eliasanti Agustina (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study explored students’ perceptions and experiences using Quizizz as a gamified learning platform to improve grammar accuracy in expository writing. Using a qualitative case study design, the research involved six purposively selected eleventh-grade students from a class of 75, representing various proficiency levels. Data were collected through structured interviews and classroom observations over four weeks to examine how students interacted with Quizizz during grammar lessons. The findings indicate that Quizizz significantly enhances student motivation and engagement by offering an interactive and enjoyable learning experience. Immediate feedback was especially helpful in improving students’ understanding of conjunctions and the simple present tense. However, challenges such as unstable internet access and limited grammatical explanations were also reported. Despite these limitations, Quizizz proved to be a valuable supplementary tool when combined with teacher guidance. It supports student-centered learning and increases participation in digital classrooms. Grounded in constructivist and gamification learning theories, the study highlights the importance of interactive and autonomous learning environments. The findings suggest that while Quizizz alone may not suffice for deep grammar instruction, its integration with conventional teaching methods can enrich grammar learning. Practical insights are also offered for educators aiming to implement gamified learning tools effectively, particularly for scaffolding complex grammar topics in diverse classrooms.